REFLEKSJE O NARRACJI DONBASKIEJ W KULTURZE I LITERATURZE UKRAIŃSKIEJ Z PERSPEKTYWY XXI WIEKU - Agnieszka Matusiak (Rusycystyczne Studia Literaturoznawcze, 2018)
The article is devoted to political, cultural and mental diversity of Donbass from the rest of Ukraine. The author shows the uniqueness of this region as a result of a complex and contradictory history, as well as the effect of permanent social, economic and ethnocultural processes of a colonial and totalitarian character. This is the reason for the hybrid identity of local residents. Later on, more space is devoted to the work of two writers — Ukrainian-speaking Serhiy Zhadan and Ukrainian-Russian-speaking Vladimir Rafeenko.